Periodic boundary value problems for impulsive neutral differential equations with multi-deviation arguments - Ye,Guobing (2010)
We develop the impulsive inequality and the classical lower and upper solutions, and establish the comparison principles. By using these results and the monotone iterative technique, we obtain the existence of solutions of periodic boundary value problems for a class of impulsive neutral differential equations with multi-deviation arguments. An example is given to demonstrate our main results. Mathematical subject classification: Primary: 34A37; Secondary: 34k10.